When Perception Becomes Reality and Truth is Relative: Spin Strategies and Political Influence over Media Reporting in Macedonian Media - Trajkoska , Žaneta (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The power of politicians presenting itself in front of the public rests in the media, so politicians are likely to use the media to create the preferred media frames and to set the agenda (agenda setting). Worldwide, spin-doctors have their own influence in the modeling of the media reality, processes that are comparable in Macedonia as well. The paper strive to describe the presence of the spinning in Macedonia and its impact on the news content. Furthermore, it deals with the spinning tactics and their manifestation in the political communication, explaining the models in which political spinning is functioning in Macedonia. Main research questions are focused on: (1) how does the process of creating the news is carry out and what affects the news content production; (2) what specific strategic doctrines spin-doctors are using to influence the process of daily reporting and to participate in the creation of the media reality; (3) how the spin-doctors present information and communicate with the public and what methods and tools are characteristic for spinning cycles.